Ending poverty & hunger: IFPRI and the Bill & Melinda Gates Foundation - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Launched in 2003, IFPRI’s partnership with the Bill & Melinda Gates Foundation has brought us many steps closer to our shared vision of a world free of hunger and malnutrition, where, in the words of Bill and Melinda Gates, “all lives have equal value.” This report highlights the progress we have made together, as we work to end hunger and poverty, a goal that we both agree is within reach.